Board Characteristics, Asset Quality and Financial Performance of Deposit Money Bank - Quadri, Yusuf Olamilekan; Omotosho, Ifedolapo Oluwasolape; Saheed, Daud Omotosho; Adio, Babatunde Abdullah (Copernican Journal of Finance & Accounting, 2024)
This study evaluates how the board composition and asset quality of Nigerian deposit money banks affected their financial performance. The study used a sample size of 20 out of 33 deposit money banks and an ex-post facto research design. Panel least square regression techniques were then used to assess the secondary data gathered from the audited financial records of the participating deposit financial institutions for the years 2014 to 2021. The study found that while asset quality has a negative impact on the performance of Nigerian banks, the size of the board and the makeup of the credit committee have a beneficial impact. As a result, the study came to the conclusion that board qualities and asset quality are two further elements that affect deposit money bank performance in Nigeria. In order to ensure that its members are appropriately diverse and in compliance with the Corporate Governance Code, the study proposed that the size of deposit money institutions' boards be rationalized. In order to guarantee that banks are not exposed to excessive risk, it was also advised that the Central Bank of Nigeria should keep an eye on the operations of the credit committee.